Effect of Friction Stir Welding Process Parameters on Depth of Surface Defect on Aluminum Material AA6061-T651 - Ardhiansyah, Mohammad; Mulyadi, Mulyadi; Iswanto, Iswanto (AutoMech : Jurnal Teknik Mesin, 2022)
Aluminum is widely used in the industrial world, usually, the connection of aluminum often uses the rivet method and Tungsten Inert Gas (TIG) welding. Many welding methods can be used for joining aluminum, but the Friction Stir Welding method is the most recommended method because the process is simple and does not pose a health hazard. This research was conducted to determine the contribution of the Friction Stir Welding (FSW) process parameter to the depth of surface defects using a hexagonal pin geometric tool. Welding material uses AA6061-T651 aluminum and uses 4 parameters: tool speed, welding speed, concave shoulder angle, and tool tilt angle. In this process, the Taguchi method is used to study the effect of parameters with a predetermined process variation. From the results of ANOVA with signal to noise, more minor is better, we get a significant factor in the depth of surface defects. The results obtained are surface defects close to 0 mm or parallel to the specimen surface, in specimen 16 with a tool slope parameter of 2Â°, a tool rotation speed of 3022 rpm, welding speed of 60 mm/m, and a concave shoulder angle of 11Â°.